2020
DOI: 10.1055/s-0040-1716792
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Brain Arteriovenous Malformations: Surgical Timing and Outcomes—A Retrospective Study of 25 Cases

Abstract: Background One important problem in treatment of ruptured brain arteriovenous malformations (bAVMs) is surgical timing. The aim of the study was to understand which parameters affect surgical timing and outcomes the most. Materials and Methods Between January 2010 and December 2018, 25 patients underwent surgery for a ruptured bAVM at our institute. Intracerebral hemorrhage (ICH) score was used to evaluate hemorrhage severity, while Spetzler-Martin scale for AVM architecture. We divided patients in two groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this section, we present the current evidence regarding immediate and delayed treatment of bAVMs. Whilst there is currently a lack of studies comparing the two paradigm approaches, we have summarized individual studies looking at either of the two approaches when feasible, with results summarized in Table 1 [ 6 - 15 ]. Traditionally, indications for emergency or immediate intervention of ruptured bAVMs include patients with life-threatening hematoma and its associated mass effects, deteriorating neurological status, and the presence of aneurysms[ 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we present the current evidence regarding immediate and delayed treatment of bAVMs. Whilst there is currently a lack of studies comparing the two paradigm approaches, we have summarized individual studies looking at either of the two approaches when feasible, with results summarized in Table 1 [ 6 - 15 ]. Traditionally, indications for emergency or immediate intervention of ruptured bAVMs include patients with life-threatening hematoma and its associated mass effects, deteriorating neurological status, and the presence of aneurysms[ 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study has shown that delayed conclusive treatment yields more favorable functional outcome[ 6 ], and that both approaches are influenced by different factors, wherein early intervention is influenced by the ICH score, while the delayed intervention is influenced by the bAVM microarchitecture as defined by the Spetzler-Martin grades. In said study, the mortality rate between the early and delayed group was also significantly different, although this should be interpreted with caution, due to the higher likelihood of high-risk emergency comorbidities accompanying cases of early treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Arteriovenous shunts (also referred to as arteriovenous malformations, or AVMs) can pathologically arise in numerous tissues including the liver ( Copel et al, 2018 ), coronary circulation ( Gatzoulis et al, 2018 ), lungs ( Cartin-Ceba et al, 2013 ), and brain ( Principles of Neurological Surgery, 2012 ), often with detrimental effects on health and mortality. In particular, AVMs in the brain are an important cause of haemorrhagic stroke, and surgical treatment options are invasive and limited ( Derdeyn et al, 2017 ; Di Bartolomeo et al, 2021 ). The lack of arteriovenous shunts in healthy vasculature suggests there must be additional mechanisms beyond shear stress which regulate remodelling and prevent shunting, as originally proposed by ( Pries et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%